Impact of Brief Counseling on Nonurgent Prior- versus Never-counseled Samples. Issue 2 (3rd April 2019) - Blau, Gary; DiMino, John
ABSTRACT: The purposes of this study were to distinguish prior- versus never-counseled nonurgent University Counseling Center (UCC) clients and to test if brief counseling had a differential impact on these two samples. The prior-counseled sample (n = 100) was more prepared for counseling, had a lower stigma for seeking help, as well as lower social connectedness and life satisfaction versus the never-counseled sample (n = 109). After brief counseling (median of four sessions after triage), the prior-counseled group (n = 33) had significantly higher social connectedness, self-esteem, and life satisfaction, while only social connectedness of the never-counseled group (n = 31) increased.